2018
DOI: 10.22192/ijcrms.2018.04.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric comorbidities among the patients of epilepsy attending general hospital psychiatric unit

Abstract: Background: Depression is most common psychiatric disorder in patients with epilepsy and it is the significant cause of morbidity. 1 Upto 50-60 percent of patients with epilepsy may develop psychiatric complications, particularly depression, anxiety, and psychotic disorders. 2 There is growing evidence of biological link between depression and epilepsy, and significant factors involved are the biological amines and gamma amino butyric acid (GABA) 3 along with other neurobiological and psychosocial factors. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The magnitude of common mental disorders in the current study is in line with the findings done in Mexico [24] (36.4%) and in India (32.5%) [25,26]. However, this study has revealed much lower magnitude of comorbidity of common mental illness than the result done in Zambia (53.7%) [27], Brazil (54.1%) [28], India (50.0%) [29], and Turkey(40.5%) [30]. The higher prevalence in Zambia and Brazil might be because of differences in inclusion criteria and instrument variation for screening mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…The magnitude of common mental disorders in the current study is in line with the findings done in Mexico [24] (36.4%) and in India (32.5%) [25,26]. However, this study has revealed much lower magnitude of comorbidity of common mental illness than the result done in Zambia (53.7%) [27], Brazil (54.1%) [28], India (50.0%) [29], and Turkey(40.5%) [30]. The higher prevalence in Zambia and Brazil might be because of differences in inclusion criteria and instrument variation for screening mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…A hospital-based cross-sectional study conducted in the northeastern part of India prevailed that 18% of PWE experiences depression and the Presence of partial seizures, frequent seizures, long duration of epilepsy and poor compliance to the antiepileptic drug were significantly associated with depression [19]. Another institutional-based cross-sectional study conducted on patients attending psychiatric outpatient epilepsy clinic in the psychiatry department of Amritsar city in India shows that 40% of the participant suffers from depression (with 22.5% severe depression and 17.5% moderate depression) and also being female and on antiepileptic medication also factors associated with depression [20].…”
Section: Introductionmentioning
confidence: 99%
“…A cross‐sectional study conducted in Canada among PWE to determine the magnitude and associated factors of anxiety found that the prevalence of anxiety was 40.0%, having depression, medication side effects, smoking and illicit substance use were significantly associated with anxiety (Pham et al., 2017). A study conducted in India among PWE shows that 50% of the study participants develop psychiatric comorbidity (Rani et al., 2018). A case–control study conducted in India reported that PWE had higher anxiety of 32.5% as compared with asthmatic patient control (17.5%) and normal control (7.5%), had longer duration of seizures, had increased frequency of seizures, had recent reappearance of seizures, had anti‐convulsant polypharmacy, had poor compliance with medications, and family history of seizures is an independent predictive factor (Amruth et al., 2014).…”
Section: Introductionmentioning
confidence: 99%